1993
DOI: 10.1021/bi00083a037
|View full text |Cite
|
Sign up to set email alerts
|

Novel heteronuclear methods of assignment transfer from a diamagnetic to a paramagnetic protein: application to rat cytochrome b5

Abstract: 15N and 1H resonance assignments for backbone and side-chain resonances of both equilibrium forms of rat ferricytochrome b5 have been obtained, using a combination of novel heteronuclear assignment transfer methods from the known assignments of the diamagnetic protein [Guiles, R. D., Basus, V. J., Kuntz, I. D., & Waskell, L. A. (1992) Biochemistry 31, 11365-11375] and computational methods which depend on an accurate determination of the orientation of the components of the susceptibility tensor. The transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
42
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 45 publications
8
42
0
Order By: Relevance
“…The change in the shift of Gly 42 is difficult to interpret in the presence of a modified dipolar field, but the NOE data have been used to propose that the haem in the B form is rotated by a few degrees about the haem normal with respect to the A form, in addition to being flipped over about the 5CH-15CH axis. The proposed sense of rotation shifts the 5CH of the B form towards the 20CH position found in the A form (Pochapsky et al 1990), and Guiles et al (1993) found a rotation of 5-10 ° between the magnetic susceptibility tensors in the A and B forms of rat cytochrome b 5 which they took to be a confirmation of the earlier conclusion. It is important to note that quite different reference frames apply: the NOE data relate the position of one methyl group in the protein to the position of the haem whereas the magnetic axes are determined with respect to the protein structure and do not provide any definitive information about the orientation of the haem itself.…”
Section: Resultssupporting
confidence: 61%
“…The change in the shift of Gly 42 is difficult to interpret in the presence of a modified dipolar field, but the NOE data have been used to propose that the haem in the B form is rotated by a few degrees about the haem normal with respect to the A form, in addition to being flipped over about the 5CH-15CH axis. The proposed sense of rotation shifts the 5CH of the B form towards the 20CH position found in the A form (Pochapsky et al 1990), and Guiles et al (1993) found a rotation of 5-10 ° between the magnetic susceptibility tensors in the A and B forms of rat cytochrome b 5 which they took to be a confirmation of the earlier conclusion. It is important to note that quite different reference frames apply: the NOE data relate the position of one methyl group in the protein to the position of the haem whereas the magnetic axes are determined with respect to the protein structure and do not provide any definitive information about the orientation of the haem itself.…”
Section: Resultssupporting
confidence: 61%
“…9 These redox shifts, not yet fully understood, might have implications in the electron-transfer process. Similar effects have been reported for Fe n+ (Cys4) rubredoxins, 10 as well as for ferredoxins 11 and putidaredoxins, 12,13 which contain an [Fe 2 S 2 ] n+ cluster, whereas, to our knowledge, no such effects have been reported so far for any protein of the [Fe 4 S 4 ] n+ family.…”
mentioning
confidence: 99%
“…The only residue which has not been identified is Pro90. 15 N HSQC spectra are very similar to those of the native protein [37,38]. 15 N shift differences larger than 1 ppm between backbone amide protons in the native and in the modified proteins are detected for residues 1, 3, 31, 44, 56, 57, 58, 61, 63, 64, 65, 66, 68, 83, 85, and 93.…”
Section: Nmr Spectramentioning
confidence: 67%